Free $Q$-distributive lattice over an $n$-element chain - Monteiro, Luis (2004)
In this note we provide an explicit construction of $FQ({\bf n})$, the free $Q$-distributive lattice over an $n$-element chain, different from those given by Cignoli [4] and Abad--Díaz Varela [1], and prove that $FQ({\bf n})$ can be endowed with a structure of a De Morgan algebra.